2017
DOI: 10.1016/j.jconrel.2017.08.013
|View full text |Cite
|
Sign up to set email alerts
|

The integration of triggered drug delivery with real time quantification using FRET; creating a super ‘smart’ drug delivery system

Abstract: The ability to control drug release at a specific physiological target enables the possibility of an enhanced therapeutic effect with reduced off-target toxic side effects. The discipline of controlled drug release has grown to include most areas of medicine with examples in the literature of targeted drug delivery to the majority of organs within the human body. In addition, a variety of external stimuli used to meditate the drug release process have also been investigated. Nonetheless, the concurrent real ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 38 publications
0
10
0
Order By: Relevance
“…The cis ‐to‐ trans isomerization can be achieved by illumination with Vis light (λ > 400 nm) or heating ( Scheme a) . SP is a hydrophobic moiety and able to isomerize to hydrophilic trans conformation, merocyanine (MC), under UV irradiation via intramolecular carbon–oxygen bond breakage (Scheme b) . Similar to AZO, Vis light or heating can induce the trans ‐to‐ cis isomerization.…”
Section: Uv/vis Light Controlled Drug Delivery Systemsmentioning
confidence: 99%
“…The cis ‐to‐ trans isomerization can be achieved by illumination with Vis light (λ > 400 nm) or heating ( Scheme a) . SP is a hydrophobic moiety and able to isomerize to hydrophilic trans conformation, merocyanine (MC), under UV irradiation via intramolecular carbon–oxygen bond breakage (Scheme b) . Similar to AZO, Vis light or heating can induce the trans ‐to‐ cis isomerization.…”
Section: Uv/vis Light Controlled Drug Delivery Systemsmentioning
confidence: 99%
“…In 2017, Aibani et al investigated a novel light-responsive DDS, which showed both controlled release of the loaded therapeutic agent and simultaneous real-time analysis of the quantity of therapeutic remaining in the micellar nanocarrier ( Aibani et al, 2017 ). The micellar drug carrier was composed of an amphiphilic copolymer, which consisted of a hydrophilic PEG monomer and a hydrophobic C10 decyl chain monomer, both containing a methacrylate functional group; this amphiphilic copolymer was previously shown to be biocompatible ( Yildiz et al, 2011 ).…”
Section: Spiropyran-based Nanocarriers For Drug Deliverymentioning
confidence: 99%
“…Overall, this system shows promise for its ability to incorporate various hydrophobic APIs, thus offering a route for solubilising them. Also, drug release can be monitored by taking advantage of FRET communication between two different chromophores in the micelles’ hydrophobic core ( Aibani et al, 2017 ).…”
Section: Spiropyran-based Nanocarriers For Drug Deliverymentioning
confidence: 99%
“…These two polymer nanoassemblies were used to monitor the amount of drug remaining in the hydrophobic core in real time and detect metastatic tumors in a tissue pH-dependent manner. Aibani et al [57] exploited differences in the hydrophobic/hydrophilic balance between two isomers, spiropyran and merocyanine, to mediate drug release from a polymer micelle. The stable spiropyran with closed hydrophobic four-ring system preferentially favors a non-polar environment, whereas light irradiation can convert to its zwittrionic merocyanine counterpart with open ring, which prefers a more hydrophilic environment.…”
Section: Macromolecule-based Drug Release Monitoringmentioning
confidence: 99%